Prolyl Hydroxylase Paralogs in Nicotiana benthamiana Show High Similarity With Regard to Substrate Specificity - Mócsai, Réka; Göritzer, Kathrin; Stenitzer, David; Maresch, Daniel; Strasser, Richard; Altmann, Friedrich (Frontiers in Plant Science, 2021)
Plant glycoproteins display a characteristic type of O-glycosylation where short arabinans or larger arabinogalactans are linked to hydroxyproline. The conversion of proline to 4-hydroxyproline is accomplished by prolyl-hydroxylases (P4Hs). Eleven putative Nicotiana benthamiana P4Hs, which fall in four homology groups, have been identified by homology searches using known Arabidopsis thaliana P4H sequences. One member of each of these groups has been expressed in insect cells using the baculovirus expression system and applied to synthetic peptides representing the O-glycosylated region of erythropoietin (EPO), IgA1, Art v 1 and the Arabidopsis thaliana glycoprotein STRUBBELIG. Unlike the situation in the moss Physcomitrella patens, where one particular P4H was mainly responsible for the oxidation of erythropoietin, the tobacco P4Hs exhibited rather similar activities, albeit with biased substrate preferences and preferred sites of oxidation. From a biotechnological viewpoint, this result means that silencing/knockout of a single P4H in N. benthamiana cannot be expected to result in the abolishment of the plant-specific oxidation of prolyl residues in a recombinant protein.